Mammalian Epidermis: A Compendium of Lipid Functionality - Vietri Rudan, Matteo; Watt, Fiona M. (Frontiers in Physiology, 2022)
Mammalian epidermis is a striking example of the role of lipids in tissue biology. In this stratified epithelium, highly specialized structures are formed that leverage the hydrophobic properties of lipids to form an impermeable barrier and protect the humid internal environment of the body from the dry outside. This is achieved through tightly regulated lipid synthesis that generates the molecular species unique to the tissue. Beyond their fundamental structural role, lipids are involved in the active protection of the body from external insults. Lipid species present on the surface of the body possess antimicrobial activity and directly contribute to shaping the commensal microbiota. Lipids belonging to a variety of classes are also involved in the signaling events that modulate the immune responses to environmental stress as well as differentiation of the epidermal keratinocytes themselves. Recently, high-resolution methods are beginning to provide evidence for the involvement of newly identified specific lipid molecules in the regulation of epidermal homeostasis. In this review we give an overview of the wide range of biological functions of mammalian epidermal lipids.